Expression of cyclooxygenase-2 in colorectal adenocarcinoma is associated with p53 accumulation and hdm2 overexpression - Ratchada Cressey (2018)
Elevated cyclooxygenase-2 (COX-2) expression has been observed in various types of cancer. Induction of COX-2 expression has been reported to increase invasiveness and angiogenesis of tumours. While COX-2 overexpression has been repeatedly proven to promote tumor growth, little is known about what initiates its induction. There has been evidence to suggest that COX-2 expression is normally suppressed by wild-type p53 but not mutant p53, suggesting that loss of p53 function may result in the induction of COX-2 expression. Loss of p53 function is not only caused by gene mutation, but also through the overexpression of its negative regulator, so called human double minute 2 (hdm2). The aim of this study was to examine the correlation between COX-2 overexpression, p53 accumulation and HDM2 overexpression, as indications of p53 anomalies, and their relationship to clinicopathologic features of colorectal adenocarcinoma. Tumor tissues and the adjacent normal mucosa were obtained from 73 colorectal cancer patients who underwent curative resection at Maharaj Nakorn Chiang Mai Hospital. Protein levels of COX-2, p53 and HDM2 were determined by Western blot analysis. No normal colorectal tissues possessed detectable levels of COX-2, p53 or HDM2. In contrast, 38.3% (28 cases), 54.8% (40 cases) and 8.2% (6 cases) of tumour tissues were found to express COX-2, p53 and HDM2, respectively. Interestingly, there was a significantly positive relationship between COX-2 overexpression and p53 accumulation and/or HDM2 overexpression (P=0.007). Higher COX-2 overexpression was observed in p53-accumulated or HDM2 overexpressed-tumours (22/43 cases, 51.1%) in comparison to tumours with no evidence of p53 and HDM2 alterations (6/30 cases, 20%). The results obtained from this study indicate that overexpression of COX-2 is frequently associated with p53 protein accumulation and HDM2 overexpression, therefore the COX-2 overexpression observed in colorectal cancer cells may be partly due to the dysfunction of p53. Although mutation of p53 has been previously reported to be associated with COX-2 induction, to our knowledge, this is the first study to show the relationship between HDM2 overexpression and COX-2 overexpression. © 2005 Elsevier Ireland Ltd. All rights reserved.